π-Cipher: Authenticated Encryption for Big Data - Gligoroski, Danilo; Mihajloska, Hristina; Samardjiska, Simona; Jacobsen, Håkon; Erlend Jensen, Rune; El-Hadedy, Mohamed (Springer International Publishing, 2014)
In today’s world of big data and rapidly increasing telecommunications, using secure cryptographic primitives that are parallelizable and incremental is becoming ever more important design goal. π-Cipher is parallel, incremental, nonce based authenticated encryption cipher with associated data. It is designed with the special purpose of providing confidentiality and integrity for big data in transit or at rest. It has, as an option, a secret part of the nonce which provides nonce-misuse resistance. The design involves operations of several solid cryptographic concepts such as the Encrypt-then-MAC principle, the XOR MAC scheme and the two-pass sponge construction. It contains parameters that can provide the functionality of tweakable block ciphers for authenticated encryption of data at rest. The security of the cipher relies on the core permutation function based on ARX (Addition, Rotation and XOR) operations. π-Cipher offers several security levels ranging from 96 to 256 bits.
Keywords: Authenticated encryption, AEAD, parallelizability, incrementality, nonce-misuse resistance, sponge construction